Strategy to Increase Contract Farming Satisfaction on Red Chili Farmer with The Hortikultura Lestari Cooperation (Evidence : Dukuh Dempok Village Wuluhan District) - Hesti Herminingsih (UPT Penerbitan Universitas Jember, 2016)
One of the many commodities that are planted by farmers in Dukuh Dempok, Wuluhan Jember is red chili. Most of the red chili farmers in Dukuh Dempok have contract farming with Hortikultura Lestari Cooperation. Hortikultura Lestari Cooperatio. The Hortikultura Lestari cooperation is the one cooperation in Jember that have contract with PT. Heinz ABC as a grower for the company. Research’s location is purposively defined based on red chili farmer in Dukuh Dempok has a number of farmers who partnered the most. Data collection was done through discussions, interviews, observation and study of the literature. The purpose of the research was to examine the efforts that can be done to improve the satisfaction of farmer. FFA (Force Field Analysis) is used to formulate the effort that can be done to improve the satisfaction of farmers. The results showed score for IFAS ( Internal Strategic Factor Analysis Summary ) is 2.70 . The resulting scores for EFAS (external Strategic Factor Analysis Summary ) is 2.60 . From the results of IFAS and EFAS, it can be determined the position of the organization in “Growth” category . The recommended strategy is concentration through horizontal integrated. This strategy is part of the growth strategy and can be done by establish cooperation with other farmers to strengthen small holder farmer group.